2021
DOI: 10.1159/000519150
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Blood Flow as a Predictor of Recurrence of Macular Edema after Intravitreal Ranibizumab Injection in Central Retinal Vein Occlusion

Abstract: <b><i>Introduction:</i></b> To investigate the relationship between retinal blood flow and the presence or absence of macular edema (ME) recurrence after intravitreal ranibizumab injection (IRI) in patients with central retinal vein occlusion (CRVO). <b><i>Methods:</i></b> We reviewed the medical records of 16 eyes with ME associated with CRVO. All eyes had received pro re nata IRI. Repeat IRI was performed if the central macular thickness was ≥300 µm. At 12 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Research has shown that subfoveal choroidal thickness (SCT) and choroidal blood flow are significantly higher in eyes with CRVO than in unaffected fellow eyes [1,2,9,10] and that both change significantly in response to IRI [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that subfoveal choroidal thickness (SCT) and choroidal blood flow are significantly higher in eyes with CRVO than in unaffected fellow eyes [1,2,9,10] and that both change significantly in response to IRI [10][11][12].…”
Section: Introductionmentioning
confidence: 99%